Design of Minutes of Meeting System Using Google Speech to Text API - Adarsh Bhat, Akshatha M, Janardhana Raju S, Vidyasagar K N, Manjunath G Asuti (International Journal of Advanced Science and Technology, 2020)
Digital dictation is a modern game changing trend as it is trying to make the use of pen and paper obsolete as the usage of pen and paper in this fast going world can be a tedious job and is not environment friendly. Any form of data can be searched digitally with just voice commands and speeches/voices can be transformed into text instantly with the latest AI and ML tools . Google Speech to Text API is one of them. This paper presents use case(Minutes of Meeting) and brief analysis of Google speech to text API for Automatic Speech Recognition(ASR) with its implementations for corporate and non-corporate businesses .This can be further enforced in multiple disciplines like medical transcriptions, automation, advanced personal assistance, in education for accelerating the process of learning